2016
DOI: 10.1007/s40139-016-0113-7
|View full text |Cite
|
Sign up to set email alerts
|

Pluripotent Stem Cell-Derived Hepatocyte-like Cells: A Tool to Study Infectious Disease

Abstract: Purpose of Review Liver disease is an important clinical and global problem and is the 16th leading cause of death worldwide and responsible for 1 million deaths worldwide each year. Infectious disease is a major cause of liver disease specifically and overall is even a greater cause of patient morbidity and mortality. Tools to study human liver disease and infectious disease have been lacking which has significantly hampered the study of liver disease generally and hepatotropic pathogens more specifically. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 95 publications
(127 reference statements)
0
15
0
Order By: Relevance
“…Historically, hepatoma cell lines have been used for in vitro cell culture models to study infectious disease, but these cells do not always accurately recapitulate the functioning of primary human hepatocytes making the study of hepatotropic infections such as Hepatitis C (HCV), which has a narrow host range, challenging (92). However, researchers found that hepatocytes derived from iPSCs provided an available source of cells with a consistent genetic background that were permissible to HCV infection and completion of the HCV life cycle (93, 94).…”
Section: Modeling Disease Using Patient Derived Ipsc Differentiated Tmentioning
confidence: 99%
“…Historically, hepatoma cell lines have been used for in vitro cell culture models to study infectious disease, but these cells do not always accurately recapitulate the functioning of primary human hepatocytes making the study of hepatotropic infections such as Hepatitis C (HCV), which has a narrow host range, challenging (92). However, researchers found that hepatocytes derived from iPSCs provided an available source of cells with a consistent genetic background that were permissible to HCV infection and completion of the HCV life cycle (93, 94).…”
Section: Modeling Disease Using Patient Derived Ipsc Differentiated Tmentioning
confidence: 99%
“…The necessity to generate data on the potential toxicity of at least 30,000 compounds, is expected to require up to 10 million animals [17]. In one study, iPSCs were derived from patients with α1antitrypsin (A1AT) deficiency [18], and through high-throughput screening, a compound that significantly reduced defective A1AT within the cytoplasm was identified [19]. As a result, iPSCs from diseased donors are being investigated for other conditions, including hypercholesterolaemia [20], glycogen storage disease [2023], Gaucher's disease [24], hereditary tyrosinaemia [20], hereditary cholestasis [18] and defective mitochondrial respiratory chain complex disorder [23].…”
Section: Hepatotoxicitymentioning
confidence: 99%
“…This will be of particular use for enhancing the resolution of GWAS validation studies and in examining subtle phenotypes. It is also important to note that iPSC‐derived hepatocytes can be used to study infectious liver disease, such as hepatitis B and C viruses and the liver stages of the Plasmodium life cycle . In this context, iPSC hepatocytes could be particularly useful to probe the variation of host responses to such infections …”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…It is also important to note that iPSC-derived hepatocytes can be used to study infectious liver disease, such as hepatitis B and C viruses and the liver stages of the Plasmodium life cycle. (70) In this context, iPSC hepatocytes could be particularly useful to probe the variation of host responses to such infections. (71) Taken together, our understanding of liver disease and development will benefit from continued efforts to generate stem cell-derived liver cells with reduced donor variability and greater maturity in more complex, but scalable, configurations.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%